APPLICATION OF LARGE PRESTRESS STRANDS IN PRECAST/PRESTRESSED CONCRETE BRIDGES - Akhnoukh, Amin K (Civil Engineering Journal, 2020)
The objective of this research is to investigate the advantage of using large-diameter 0.7-inch (18 mm) strands in pretention applications. Large-diameter strands are advantageous in bridge construction due to the increased girders capacity required to sustain exponential increase in vehicle numbers, sizes, and weights. In this research, flexure capacity of girders fabricated using 0.7-inch (18 mm) diameter strands will be calculated and compared to bridge capacities constructed using smaller strands. Finally, two similar bridge sections will be designed using 0.6-inch (15 mm) and 0.7-inch (18 mm) diameter strands to quantify the structural advantages of increased strand diameter. The research findings showed that a smaller number of girders is required for bridge construction when larger strands are used. Four girders are required to design the bridge panel using high performance concrete and large diameter strands, as compared to 6 girders required when regular concrete mix designs and normal size strands are used. The advantages of large strands and high-performance concrete mixes include expedited construction, reduced project dead loads, and reduced demand for labor and equipment. Thus, large strands can partially contribute to the improvement of bridge conditions, minimize construction cost, and increase construction site safety.